2019
DOI: 10.3758/s13415-019-00711-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral responses to self-initiated action during social interactions

Abstract: Social interaction involves self-initiated actions that engage subjective awareness of one's own volition. Individuals with social communication needs or social anxiety find it particularly difficult to initiate social interactions. However, extant studies have not specifically addressed how perceived exclusion may influence self-initiated actions during social interaction. As a first step to address this question, we scanned 24 healthy adults participating in a Cyberball game with two fictive players. By cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…In imaging findings, we demonstrated the differences between EX and FG in the neural processes of self-initiated actions. Replicating earlier work with a smaller sample size [17], ball toss during EX as compared to FG engaged higher activity in bilateral temporal and occipital cortex, including the fusiform gyrus, anterior pre-SMA, right inferior frontal cortex, bilateral thalamus, bilateral inferior parietal cortex, including the temporal parietal junction, pgACC, dorsal ACC and midcingualte cortex. Age was associated with less activation of the pgACC in men and women combined.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In imaging findings, we demonstrated the differences between EX and FG in the neural processes of self-initiated actions. Replicating earlier work with a smaller sample size [17], ball toss during EX as compared to FG engaged higher activity in bilateral temporal and occipital cortex, including the fusiform gyrus, anterior pre-SMA, right inferior frontal cortex, bilateral thalamus, bilateral inferior parietal cortex, including the temporal parietal junction, pgACC, dorsal ACC and midcingualte cortex. Age was associated with less activation of the pgACC in men and women combined.…”
Section: Discussionsupporting
confidence: 63%
“…Imaging studies showed that social exclusion as compared to inclusion engaged the insula, dorsal anterior cingulate cortex and other prefrontal cortical regions [6,[10][11][12][13][14][15]; see [16] for a review), cortical circuits that have been implicated in processing negative emotions and salient events. In recent work using the Cyberball task, we showed that social exclusion, as compared to a "fair game" scenario, encumbered self-initiated actions and engaged distinct neural processes during self-initiated actions [17,18].…”
Section: Introductionmentioning
confidence: 89%
“…The inferior temporal cortex is involved in complex visual processing, face perception, recognition of numbers and objects, social cognition, and memory (Conway, 2018). The precuneus is involved in mental imagery concerning the self (Lou et al ., 2004), episodic memory (Fletcher et al , 1995), and visuospatial imagery (Oshio et al , 2010), as well as mental effort (Zhang and Li, 2010, 2012) and social cognition (Wang et al ., 2019). Along with the precuneus, the PCC has been implicated in awareness, arousal (Le et al , 2019), and episodic memory (Nielsen et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…There were approximately 61 trials of observation in OB; 23 trials each of observation, ball tossed to, and from the participant in FG; and 51 trials of observation, and 6 trials each with ball tossed to and from the participant in EX. Data from a subsample of the current group was reported in previous studies (Wang et al, 2019a(Wang et al, , 2019b.…”
Section: Assessments and Behavioral Taskmentioning
confidence: 99%
“…Previous studies have employed RT to assess behavioral responses to ostracism, with speeded and prolonged RT reflective of social approach and avoidance, respectively (Kothgassner et al, 2017;Will et al, 2016a). Behavioral performance in the Cyberball task has been investigated in relation to neural responses to ostracism in our previous work (Wang et al, 2019b) though it remained unclear whether PB also plays a role in modulating the RT. We tested the hypothesis that social exclusion would elicit activations in the AI, dACC/dmPFC, and MFG.…”
Section: Introductionmentioning
confidence: 99%